Analyzing the influence of integrated café spaces on library user engagement through third place theory - Prijana, Prijana; Rahima, Marsya; Raquel Theresia, Gwina; Bifakhlina, Febriyanti (Jurnal Informatio, 2026)
Background: Modern libraries are evolving into multidimensional activity centers, focusing not only on providing information but also on comfort and social interaction. Younger generations such as Gen Z and Millennials view libraries as social spaces that blend academic activities with relaxation. One innovation introduced is the presence of cafés, which are part of the "third place" concept—a space outside the home and campus for informal socializing.Purpose: This study aims to determine the influence of café presence on increased visits and user satisfaction, assess the extent to which the third place concept supports social and academic needs, identify the main elements of attraction, and compare perceptions among students.Methods: This study employs a quantitative approach by distributing an online questionnaire to students of Padjadjaran University as respondents. Data were collected in nominal and ordinal forms through open-ended questions, closed-ended questions, and Likert scales. The study was conducted over ten days in the environment of the Kandaga Library at Padjadjaran University.Results: The café significantly increased library visits and satisfaction, with users appreciating its role in supporting both academic work and social interaction.Conclusions: The presence of a café can enhance the appeal and frequency of visits to the library. The café is not only a place to relax but also an informal collaboration space that supports contemporary learning styles.